Analisis Pengaruh Demokrasi, Jumlah Penduduk, dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi di Indonesia - Atri Alvinda; Wina Risti Hafipah; Ratu Aulia Jasmine; Neli Aida; Muhammad Mufti Hudani; Qurrota Ayu Nindien (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to examine the influence of democracy, population size, and the Human Development Index (HDI) on economic growth in Indonesia during the period 2019-2023. Provincial panel data in Indonesia were obtained from official sources such as the Central Statistics Agency (BPS). The Common Effect Model (CEM) was selected as the panel approach based on the results of the Chow test and the Lagrange Multiplier test. Before testing the hypotheses (t-test and F-test) and calculating the coefficient of determination (R2), classical assumptions were tested. Based on the research findings, it can be concluded that Democracy (X1) has a significant positive effect on economic growth in Indonesia, while Population Size (X2) and HDI (X3) do not have a significant effect on Economic Growth (Y). The R² value of 7.13% indicates that these three variables only explain a small portion of the variation in economic growth.